(3GdehLR aj GdfMhs - (3CHhHcQ eMeO Hf GdSQj Hf Sgd GdeYQha HGHf GdSQGL,J (B316 (3g` s ((3eMeO Hf EHQGgje Hf YHO dGdg GdCUHgGfi s)
(3ChdgG (B:s
(3GdcdGe jCJda ef KdGKI CTjGA(B: (3GSe haYd hUQa s
(3BNQgG (B:s
(3fbhd ai UGdZ (B: (3SGdZ hUdN hUGWY ai SGWY Ke GdcJGH hMSHi Gddg hfYe Gdhcjd hGdeYjf s
(3LGA HBNQ GdfSNI HNW GdfGSN cJHJg ef fSNI ebQhAI Ydi GdTjN CHj Ydi GdfMhi UGMH CHj HcQ GdSQGL hYGQVJg HfSNI HZOGOjI Ydi XgQgG (B: (3CedGg YdfjG CHh HcQ eLdSG EedGA hGHJOC Hg ai SfI CQHY hKdGKeGFI hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136s
Keywords: (3GdfMhs